A collaborative operation mode of energy storage system and train operation system in power supply network - Yang, Songpo; Chen, Yanyan; Dong, Zhurong; Wu, Jianjun (Energy (Oxford), 2023)
An advanced metro operation system is becoming imperative for promoting energy sustainability and commuting efficiency with the rapid developments of metro construction in cities. To improve energy sustainability, two different kinds of energy-saving devices have been introduced extensively in metro operations. One is operated with passive control modes, such as Regenerative Energy Devices (RED) and the other is operated with active control modes, such as Energy Storage Devices (ESD). Introducing them into one integrated power supply network in the metro system, a smart control module of the supply system should be well designed to avoid the using conflicts based on a time separation approach. Thus, we first formulate a collaborative mode between the device control and the train operation by using a discrete-time measurement method. This effect is also particularly noticeable in train timetable optimization. Then, a timetable optimization model incorporating train runs, device control, and passenger demand is introduced for trading off energy consumption, infrastructure investment, and travel time. The non-dominant sorting genetic algorithm (NSGA-II) is developed and the genetic operators are redesigned based on graph presentations. Finally, a numerical example shows that the energy efficiencies could be improved by 6.36% and 36.72% from RED and ESD systems respectively. •An integrated power supply system is built in metro system.•A collaborative control mechanism is developed for multiple energy-saving devices.•A site selection problem of devices is introduced considering construction costs.•A NSGA-II-based algorithm is designed to solve a tri-objective optimization model.